Analisis Partisipasi Masyarakat dalam Pembangunan Desa di Desa Saluan Kecamatan Moilong Kabupaten Banggai Provinsi Sulawesi Tengah - Alviana; Yacob Noho Nani; Romy Tantu (Transbahasa, 2026)
This study aims to analyze community participation in village development in Saluan Village, Moilong District, Banggai Regency, Central Sulawesi Province based on Cohen and Uphoff’s participation theory, which encompasses decision-making, implementation, benefit utilization, and evaluation stages. A qualitative descriptive approach was employed. Data were collected through observation, interviews, and documentation involving village government officials, members of the Village Consultative Body (BPD), and community members of Saluan Village. Data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings reveal that community participation has occurred throughout all stages of village development, although the level of involvement remains uneven. In the decision-making stage, participation was reflected through attendance at Village Development Planning Meetings (MusrenbangDes), submission of development proposals, and responses to development programs. However, participation was influenced by limited public awareness and the dominance of certain groups in deliberative forums. During the implementation stage, participation was mainly demonstrated through labor contributions in mutual cooperation activities and the Cash-for-Work Program (PKT). In the benefit utilization stage, community members utilized development outcomes to support their social and economic needs. In the evaluation stage, participation was manifested through the provision of feedback, criticism, and suggestions as a form of social control. The study concludes that community participation has been present across all development stages, but greater involvement in decision-making is needed to achieve more participatory and sustainable village development.